Research on Avoidance of Energy Hole Scheme in the Wireless Mesh Network - Chunlong Lu; Yuchun Cao; Guangxue Yue (Dianxin kexue)
In order to avoid the energy hole problem in wireless mesh network, the non-uniform distribution strategy about the cluster nodes was put forward, the energy efficiency optimization equilibrium routing algorithm was designed. When the distribution of cluster nodes in the wireless mesh network met the certain relations, the network could optimize the energy consumption efficiency equilibrium. In order to provide the theory basis for reliable operation in wireless mesh network for a long time, the convergence of efficiency optimization model was theoretically proved, the constraint condition of optimizing the energy consumption efficiency equilibrium was derived, and the energy hole system avoidance model was built. The simulation results show that using this strategy can effectively relieve the energy hole problem in wireless mesh network, prolong the network life cycle and cut down the network residual energy rate.